The Determination of Satellite Orbital Decay From POD Data During Geomagnetic Storms - Ruoxi Li; Jiuhou Lei (Space Weather)
Abstract In our previous study (Li et al., 2017, https://doi.org/10.1007/s11430-016-9052-1), we derived the satellite energy‐decay with a 20‐min resolution based on the Precise Orbit Determination (POD) data, using a proximate analytic approach to represent the time variation gravitational potential. In this follow‐up study, we improved the previous approach and calculated the POD‐based energy‐decays by using a numerical integration approach. Based on the precise energy‐decays, the orbital decays and decay rates with higher accuracy and resolution were further derived. The relative deviations of the orbital decays are generally less than 10% with respect to the accelerometer‐reference. The satellite orbital decays and decay rates derived from this approach were used to study the effects of geomagnetic activities and background density on the orbital changes. Our results show that, during the severe November 2003 storm, the storm‐induced orbital decay rate increased by a factor of 8 with respect to the quiet‐time reference. This POD‐based integration approach was also applied to study the orbital changes of multiple satellites at different altitudes during the September 2017 moderate storm. It is found that the storm‐induced orbital decay rates of Swarm‐B, Swarm‐A, and Gravity Recovery and Climate Experiment satellites increased by 100%–150% depending on their altitudes. Overall, the results suggest that our integration approach has better performance than the previous approach in deriving the orbital decay rate at solar minimum or at high altitude when the atmospheric density is relatively low.